2010
DOI: 10.1590/s0102-36162010000600016
|View full text |Cite
|
Sign up to set email alerts
|

Ensaios Clínicos Randomizados na ortopedia e traumatologia: avaliação sistemática da evidência nacional

Abstract: Trabalho recebido para publicação: 02/03/10, aceito para publicação: 09/03/10. RESuMOObjetivo: Verificar se houve melhora da qualidade e quantidade dos ensaios clínicos randomizados (ECRs) publicados na literatura nacional, por meio da aplicação de escores estruturados e validados na literatura. Métodos: Selecionamos, eletronicamente, todas as edições das duas revistas indexadas e de escopo ortopédico da literatura nacional -Acta Ortopédica Brasileira (AOB) e Revista Brasileira (2000-2004 and 2004-2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In 1975, orthopedics papers comprised only 4% of all publications in the journal, but by 2005, this number had increased to 21% of all publications in the journal. We believe that the lack of changes found by De Moraes et al 16 is because a shorter period was assessed and that the analysis was performed in two periods of five years (2000-2004 and 2005-2009). In our study, we did not analyze historical trends because we considered five years to be too short to do so.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In 1975, orthopedics papers comprised only 4% of all publications in the journal, but by 2005, this number had increased to 21% of all publications in the journal. We believe that the lack of changes found by De Moraes et al 16 is because a shorter period was assessed and that the analysis was performed in two periods of five years (2000-2004 and 2005-2009). In our study, we did not analyze historical trends because we considered five years to be too short to do so.…”
Section: Discussionmentioning
confidence: 91%
“…De Moraes et al 16 assessed 22 RCTs published in RBO and AOB from 2000 to 2009. The authors did not find significant differences in quality or types of publications when comparing the first five-year period with the second one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical analysis on our own scientific production is little disseminated within orthopedics and traumatology. However, some studies have reported on the status of this scientific production and have identified the most frequent types of studies, in the light of evidence-based medicine,4, 5, 27, 28 or have attempted to compare Brazilian production with what has been published in indexed international journals 29 . The present study has the virtue of including a validated tool for assessing the quality of the scientific method, which makes this approach unique within our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials are the gold-standard studies for determining what form of treatment is best 1, 2, 3, 4, 5. However, in situations involving surgical interventions, randomization and/or blinding may not be feasible or may be difficult to implement.…”
Section: Introductionmentioning
confidence: 99%